Challenges and opportunities in the okra (Abelmoschus spp.) seed system in Benin - Blalogoe, Jelila S.; Ayenan, Mathieu A. T.; Aglinglo, Lys Amavi; N’Danikou, Sognigbe; Schafleitner, Roland; Achigan-Dako, Enoch G. (Frontiers in Sustainable Food Systems, 2025)
IntroductionWell-functioning seed systems are essential for disseminating improved crop varieties and boosting agricultural production. Understanding their functioning is key to designing tailored interventions. This study analyzed okra (Abelmoschus spp.) seed systems in the Republic of Benin, focusing on seed production, distribution, and constraints affecting the sector.MethodsA total of 296 okra growers, 79 seed producers, and 34 seed distributors were surveyed using structured questionnaires. Data were collected on seed sources, varieties, quality perceptions, and constraints. Both regulated and farmer-managed seed systems were assessed.ResultsFarmers’ seed systems supplied 90.1% of okra seed, while the regulated system accounted for 9.9%. The regulated system offered 18 varieties (including hybrids and open-pollinated varieties), while the farmer system offered 11 open-pollinated varieties. Respondents valued the germination rate and quality of regulated seed but cited high cost as a major limitation. Other critical barriers included lack of seed quality information, long distances to certified seed sales points, price disparities between imported and local seed, and limited awareness of improved variety performance.DiscussionTo address these challenges, we recommend establishing village-based agro-dealer networks and decentralized seed hubs to improve last-mile delivery in underserved areas. Complementary actions such as on-farm demonstration trials, participatory varietal evaluations, and flexible certification models could enhance farmer awareness, affordability, and seed system inclusivity. While focused on okra in Benin, the structural challenges identified are common in West African vegetable seed systems, offering valuable insights for regional interventions.